PP02 The role of in situ simulation in a quality improvement project to improve care of the deteriorating patient. (July 2018) - Clegg, Eleanor; Harrison, Tracey; Robinson, David; Credland, Tim; Jackson, Angela
Abstract : Aim: We identified there was a problem in the communication of lessons learnt from complaints or Serious Incidents (SIs). We introduced simulated scenarios to the multi-professional team working in the Emergency Department (ED) one morning each month from November 2016 to be the conduit for this information deliverance. This was part of a wider action plan to improve the care of the deteriorating patient in the department. Objectives: To improve patient care by using the education tool of simulation. Summary of work undertaken: We began by writing scenarios that reflected these difficult cases to enable learning to be shared directly with clinical staff. We introduced the monthly simulation session to run from 8 am – 10 am one morning each month. The scenarios last up to 30 min followed by an immediate debrief. We use the session to explain trust and departmental systems and processes as well as discussing the technical skills and human factors demonstrated by those involved. We recognised the importance of sharing the lessons learnt from the simulation as well as the original case with all staff. This is achieved by the completion of the 'A+E Sim News' that is placed in poster format around the department as well as disseminated electronically. We have found that staff members read the one page A4 newsletter, particularly if placed on the back of the toilet door! The sessions are monthly and after each session the lessons learnt ('A+E Sim News') are sent out within 24 hours to all staff electronically. The sessions are multi-professional and welcome feedback that is given in written format immediately after the scenario debrief. Impact on practice: The teaching sessions are becoming part of a cultural change to valuing quality education and sharing lessons learnt with the whole department. We are finding anecdotally that staff are asking when the next session is, suggesting scenarios and sharing learning by word of mouth. Each session offers us the opportunity to identify latent risks that are recorded and actioned. For example, a preeclampsia scenario identified a difficult protocol that was subsequently revised. Other scenarios have allowed us to identify the latent risks posed by knowledge of location of intralipid and other medications, and the activation of the massive haemorrhage pathway. We have identified that in situ simulation sessions can be cancelled or shortened due to clinical demands. Taking the project forward, we intend to implement a rota for delivering the monthly session to promote sustainability of the project, with involvement of the whole consultant body in facilitating sessions. In situ simulation is a powerful educational tool regardless of fidelity of the simulator used. The latent risks identified from simulation are powerful evidence that can be used to promote change. The in situ simulation programme was introduced as one facet of a quality improvement project which aimed to improve the care of the deteriorating patient. Outcomes from this project include a reduction in Serious Incidents (SIs) related to the deteriorating patient figure 2 and a reduction in emergency ICU referrals figure 3.